Kegiatan Peningkatan Ketrampilan Ibu Rumah Tangga dan Remaja Melalui Pelatihan dan Technoprenership di Kabupaten Pekalongan (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
Ketela tree / cassava is a plant that is widely found in Sambiroto Village, Pekalongan District. Abundant availability does not guarantee the welfare of the community to the potential of these resources. This is because during this time cassava is marketed in fresh form without further processing. While the young cassava leaves are only sold in the form of ikat units as vegetables. To be able to increase the selling value of cassava leaves, efforts are needed to turn it into a processed product that is of high economic value and durable. One of the processed forms of cassava leaves that are worth selling high is cassava leaf chips. Along with the abundance of resources in the form of cassava leaves that are still not optimal potential, in Sambiroto Village can be found a lot of housewives who do not work, so that a lot of their time is loose that should be if used properly can be used to entrepreneurship develop home industry, it is also conveyed by the Village Secretary about the low interest and knowledge of Mothers to entrepreneurship. So that carry out socialization and Entrepreneurship training with the target of Housewives and also Teenagers, because usually teenagers are full of ideas and innovations that may one day play a role in helping to improve the village economy. Activities carried out include entrepreneurial socialization, creative business training, digital marketing training. The result of this devotion is that I found that mothers and adolescents actually have the desire to entrepreneurship but do not yet have knowledge about entrepreneurship and develop the potential of a resource that is around.